An alternative SGR method for shallow siliciclastic rock-A case study from the Kendong uplift of the Bohai Bay Basin. (October 2021) - Wang, Yu; Jiang, Youlu; Zhao, Kai; Hu, Hongjin; Su, Shengmin; Gong, Simin
Abstract: Clay smear is an important formation mechanism of fault lateral sealing. The Shale Gouge Ratio (SGR) is often used to quantitatively predict clay smear, but the SGR mechanism only considers the clay smear of the hanging wall, ignoring the clay smear of the footwall and the influence of the mudstone distribution. Thus, the application of SGR is not effective in certain cases. In this paper, based on a dynamic evolution model of clay smear in shallow siliciclastic rocks, the problems of SGR application are analyzed and ameliorated, and the Advanced Shale Gouge Ratio (ASGR) index for evaluating clay smears is proposed. We add two factors, the clay smear of the footwall and the mudstone distribution, to the clay smear evaluation and propose two ASGR algorithms, which differ according to whether each interior point in an individual mudstone is regarded as an independent calculation unit or all interior points are taken as a whole. The ASGR index is applied to an exploration case study of the Kendong uplift of the Bohai Bay Basin. The ASGR results of fault F1 show that, the clay smear effect of the footwall is superior to that of the hanging wall in most cases, and sometimes only the footwall plays a key role in clay smear, which illustrates the importance of the clay smear of the footwall. This study reveals the ASGR as an alternative method for the fault sealing evaluation of shallow siliciclastic rocks and can serve as a helpful reference for further research in this area. Highlights: The dynamic evolution model of clay smear in shallow siliciclastic rocks is illustrated. The ASGR index considers mudstone distribution and the clay smear of both hanging wall and footwall. The mudstone distribution has an effect on the clay smear of the hanging wall and footwall. The smear of the footwall is stronger than that of the hanging wall in most cases.